The Influence of Transformational Leadership and Moderated Training for Providing Incentives on Employee Performance at The Pangkalan PSDKP Jakarta - Indra Adi Wibisono; Badawi Saluy, Ahmad (Journal of Accounting and Finance Management, 2024)
his study aims to determine the effect of Transformational Leadership and Training moderated by the provision of  incentives on Employee Performance at the Pangkalan PSDKP Jakarta. This study was conducted at the Pangkalan PSDKP Jakarta using samples of 100 respondents. The sampling technique is non-probability sampling or saturated sample. The data analysis technique used is SEM-PLS which calculations are assisted by the SmartPLS 4.0 program. Evaluation analysis of the Partial Least Square (PLS) model is carried out by evaluating the outer model and evaluating the inner model. From the results of data analysis that has been carried out, it shows that transformational leadership has a positive and significant effect on Employee Performance. Training has a positive and significant effect on Employee Performance. Incentives have a positive and significant effect on Employee Performance. Transformational Leadership moderated by Incentive provision has a positive and insignificant effect on Employee Performance. Training moderated by incentives provision has a positive and insignificant effect on employee performance. The results of the data analysis showed that the incentive variable as a moderating variable did not strengthen its effect even though it still had a positive relationship with Transformational Leadership, Training and employee performance.